THE GENESIS OF THE CARBONATIZED AND SILICIFIED ULTRAMAFICS KNOWN AS LISTVENITES: A CASE STUDY FROM THE MIHALιççιK REGION (ESKIşEHIR), NW TURKEY - Akbulut M.; Pişkin Ö.; Karayiǧit A.I. (My University, 2006)
The Mihalιççιk region (Eskişhir) in NW Turkey includes an ophiolitic assemblage with a serpentinite-matrix mélange. The serpentinites of this mélange host silica-carbonate metasomatites which were previously named as listvenites. Our mineralogical and geochemical studies revealed that these alteration assemblages represent members of the listvenitic series, mainly the carbonate rocks, silica-carbonate rocks and birbirites, rather than true listvenites (sensu stricto). Tectonic activity and lithology are principal factors that control the formation of these assemblages. Carbothatization and silicification of the serpentinite host-rock is generated by CO2, SiO2-rich H2O hydrothermal fluid which includes As, Ba, Sb and Sr. Low precious metal (Au, Ag) contents of the alteration assemblages indicate lack of these metals in the fluid. Primary assemblages of the alteration are carbonate rocks that are followed by silica-carbonate rocks and birbirites, respectively. Petrographic studies and chemical analyses suggested an alkaline and moderate to high temperature (350-400°C) fluid with low oxygen and sulphur fugacity for the carbonatization of the serpentinites. The low temperature phases observed in the subsequent silicification indicated that the fluid cooled during progressive alteration. The increasing Fe-oxide content and sulphur phases also suggested increasing oxygen and sulphur fugacity during this secondary process and silica-carbonate rock formation. The occurrence of birbirites is considered as a result of reactivation of tectonic features. These rocks are classified in two sub-groups; the Group 1 birbirites show analogous rare earth element (REE) trends with the serpentinite host-rock, and the Group 2 birbirites simulate the REE trends of the nearby tectonic granitoid slices. The unorthodox REE trend of Group 2 birbirites is interpreted to have resulted from a mobilization process triggered by the weathering solutions rather than being products of enrichment by the higher temperature hydrothermal activity. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: ESKIşEHIR-MIHALιççιK; LISTVENITE; OPHIOLITE; SILICA-CARBONATE ALTERATION; TURKEY